Challenges in Crisis Management on Environmental Health Deliveries in Malaysia - Salleh, Shahmiza; Misri, Nazattulsyima; Saufian, Ili Nuryumni; Abdul Razak, Nurfazhilah; Ishak, Mohamad Faizal; Shafie, Farah Ayuni; Megat Mokhtar, Megat Azman; Jalaludin, Juliana; Abu Bakar, Farahdilla; Mustaffa, Masniza; Kim Soon, Peter Gan; Kunju, Sahhir (National Environmental Health Association, 2021)
JULIANA BINTI JALALUDIN/Shahmiza Salleh,//Nazattulsyima Misria, Ili Nuryumni Saufian,Nurfazhilah Abdul Razak,Mohamad Faizal,Farah Ayuni Shafie, Megat Azman Megat Mokhtar,Farahdilla Abu Bakar,Masniza Mustaffa,Peter Gan Kim Soon,Sahhir Kunju